The Relationship Between Soil-Transmitted Helminths (STH) Infection and the Stunting Incidence in Toddlers at the Kedai Durian Community Health Center, Medan, Johor, in 2023 - Brian Nicolas Sanpratama Lumbangaol; Ronald Tambunan; Sanggam B, Hutagalung; Surjadi Rimbun; Adrian khu (Universitas Methodist Indonesia, 2024)
Background:Worldwide, around 1 in 4 toddlers experience stunting. Stunting can causedisorders in the form of stunted brain growth and immune systemdisorders in toddlers. Malnutrition at an early age is found to occur in thefirst 1000 days of life can increase the risk of infant and child mortality. Itis known that chronic STH infection can cause stunting in children.Purpose: this study was to determine whether there is a relationshipbetween Soil Transmitted Helminths (STH) infection and the incidence ofstunting in toddlers at the Kedai Durian Health Center, Medan Johor in2023.Research Method: this was carried out in an analytical observationalmanner with an approach using a cross-sectional design, which is onlymomentary or sees the relationship between soil transmitted helminthsinfection and the incidence of stunting in toddlers at the Kedai DurianHealth Center, Medan Johor in 2023 when the study was taking place. Thesampling technique used purposive sampling. Which is to obtain a sampleof 35 respondents based on inclusion and exclusion criteria.Results: from this study, the most respondents were children infected withSTH worms, as many as 19 respondents (54.3%), and those who were notinfected were 16 respondents (45.7%), it was obtained that the mostchildren who were stunted were 17 respondents (48.6%), and those whowere not stunted were 18 respondents (51.4%). and There is a relationshipbetween STH worm infection and stunting with (chisquare count 10.493>chisquare table (0.05(1)) 3.841, P value 0.01 and RP (3.8). [95% CI 1.37 -11.28]. From these results, it was also found that children who suffer fromSTH infection have a prevalence of stunting 3.8 times more than those whoare not infected with STH, so that STH infection is a high risk factor forstunting in toddlers.Conclusion: The results of the study found a relationship between STHinfection and the incidence of stunting